2018
DOI: 10.1002/jgh3.12056
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in celiac disease and the effect of gluten‐free diet

Abstract: Background and AimPatients with celiac disease (CD) have a poor health‐related quality of life (HR‐QOL). We assessed the QOL in patients with CD using both generic (SF‐12) and specific (CD‐QOL) questionnaires, and the effect of gluten‐free diet (GFD) on HR‐QOL.MethodsWe conducted a prospective follow‐up study based on consecutive patients of suspected CD between June 2014 and November 2015. After taking a detailed history, all patients were subjected to laboratory investigations (including complete blood count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…The study sheds light on the mental and emotional challenges associated with adhering to a glutenfree diet, revealing feelings of restriction, burden, and the need for constant vigilance. Our research indicated a lower self-reported mental wellbeing in all participants with CeD and NCGS compared to the average Dutch population, based on the most recent data available from 2016 (43), aligning with previous studies emphasizing the impact of adhering to a gluten-free diet on mental health (44,45).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study sheds light on the mental and emotional challenges associated with adhering to a glutenfree diet, revealing feelings of restriction, burden, and the need for constant vigilance. Our research indicated a lower self-reported mental wellbeing in all participants with CeD and NCGS compared to the average Dutch population, based on the most recent data available from 2016 (43), aligning with previous studies emphasizing the impact of adhering to a gluten-free diet on mental health (44,45).…”
Section: Discussionsupporting
confidence: 90%
“…The study sheds light on the mental and emotional challenges associated with adhering to a gluten-free diet, revealing feelings of restriction, burden, and the need for constant vigilance. Our research indicated a lower self-reported mental wellbeing in all participants with CeD and NCGS compared to the average Dutch population, based on the most recent data available from 2016(43), aligning with previous studies emphasizing the impact of adhering to a gluten-free diet on mental health(44, 45). Particularly noteworthy, self-reported mental wellbeing was even lower among food insecure individuals, echoing results from a prior study reporting lower reported mental health among food insecure individuals on a gluten-free diet(46).…”
Section: Discussionsupporting
confidence: 89%